Empowering Triyagan Village: A Comprehensive Service Program for Advancing Fisheries Cultivation and Aquaponics in Mojolaban District, Sukoharjo Regency - Suprapti, Endang; Mahananto; Prasetyowati, Kusriani (Journal of Community Capacity Empowerment, 2024)
The service program is carried out by holding activities to help develop and improve fisheries cultivation and aquaponics activities in Triyagan Village, Mojolaban District, Sukoharjo Regency. The methods used to achieve the intended goal are providing education regarding the importance of cultivating in the yard, training on cultivating fish in buckets, and training on aquaponic cultivation. Training on the aquaponic cultivation system, a combination of raising fish in buckets and vegetables, can increase partners' knowledge of cultivating fish in buckets. And aquaponics of kale. Partners can immediately practice Budikdamber and Aquaponik, cultivation management, and Budikdamber and Aquapoik business management. The author hopes that promoting cultivation around the home yard will increase family food security.